DIGITALIZATION - AS THE MAIN FACTOR IN THE DEVELOPMENT OF THE QUALITY MANAGEMENT SYSTEM OF THE TEXTILES INDUSTRY OF THE REPUBLIC OF UZBEKISTAN (World Bulletin of Management and Law, 2023)
In this article are discussed the impact of digitalization of the economy of the Republic of Uzbekistan on the development of a quality management system for the textiles industry.